1992
DOI: 10.3892/ijo_00000168
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of cyclin E and the retinoblastoma protein influences the effect of adjuvant therapy in breast cancer

Abstract: Abstract. Cyclin E and the retinoblastoma protein (Rb) are both important regulators of the G 1 phase in the cell cycle. Overexpression of cyclin E and lost expression of Rb has previously been observed in breast tumours at frequencies of 10-50% and 20-30%, respectively. We explored the prognostic role of cyclin E and Rb in breast cancer patients randomised for tamoxifen (TAM), CMF (cyclophosphamide, metotrexate, 5-fluorouracil) chemotherapy and radiotherapy (RT) and how their expression affects the patients' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Other studies related to RB status and prognosis have focused on the basal levels of RB but, interestingly, they also report a lack of association between RB expression and recurrence rate. 12,14,24 Out of the 57 patients with a non-functional RB pathway, only 12 were ER + and subsequently included in the analysis …”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Other studies related to RB status and prognosis have focused on the basal levels of RB but, interestingly, they also report a lack of association between RB expression and recurrence rate. 12,14,24 Out of the 57 patients with a non-functional RB pathway, only 12 were ER + and subsequently included in the analysis …”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…[11][12][13][14] Rb immunohistochemistry studies have provided conflicting results concerning prognosis and response to therapies, and also because of the use of different immunohistochemistry cutoff. 10,[14][15][16][17][18][19][20] The results reported by Derenzini et al 16 indicated that only the absence but not hyperphosphorylation of Rb protein predicts clinical outcome. However, it should be noted that immunohistochemistry expression of Rb has provided contradictory interpretations concerning correlation with RB1 gene status.…”
Section: Discussionmentioning
confidence: 97%
“…13,14,16,18,20,25,31 However, only few studies focused this issue in triple-negative breast carcinomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of cyclins, the regulatory subunits, occurs more frequently in tumors. Amplification of cyclin D, cyclin E, and cyclin B1 reported in leukemia and lymphomas and in a number of solid tumors like breast cancer might also have a prognostic value (Waltersson et al, 2009) and seem to be associated with poor prognosis (Ko et al, 2009). Finally, inactivation or loss of cellular inhibitors of CDKs during carcinogenesis or their aberrant regulation are very frequent events occurring in human cancer.…”
Section: Pharmacological Inhibitors Of Cdksmentioning
confidence: 99%